Factors associated with Trichomonas vaginalis infection in reproductive-aged women attending cervical screening in southeast of Brazil - da Silva Pinto, Gabriel Vitor [UNESP]; Bolpet, Aline do Nascimento [UNESP]; Martin, Laura Fernandes [UNESP]; Moço, Natália Prearo [UNESP]; Ramos, Bruna Ribeiro de Andrade [UNESP]; Silva, Mariana de Castro [UNESP]; Duarte, Marli Teresinha Casamassimo [UNESP]; da Rocha Tristão, Andréa [UNESP]; da Silva, Márcia Guimarães [UNESP]; Marconi, Camila [UNESP] (Elsevier, 2023)
Background: Sexually Transmitted Infections (STIs) can be caused by viruses, bacteria, and parasites. The World Health Organization estimated more than 300 million new global cases of curable STIs among individuals of reproductive age. Infection by Trichomonas vaginalis is one of the most prevalent curable STI. Despite the current treatments available, the diagnosis of T. vaginalis can be difficult, and the resistance to the treatment increased concern for the healthcare system. Objectives: The aim of this study was to determine the prevalence and factors associated with Trichomonas vaginalis infection among women of reproductive age attending community-based services for cervical screening. Patients and methods: A total of 1477 reproductive-aged women attending 18 Primary Health Care Units in Botucatu, Brazil, from September to October 2012, were enrolled. A structured questionnaire was used for individual face-to-face interviews for obtaining data on sociodemographic, gynecologic, and obstetrics history, sexual and hygiene practices, among others. Cervicovaginal samples were obtained for detection of T. vaginalis by culture using Diamond's medium and microscopic vaginal microbiota classification according to Nugent. A multivariable logistic regression analysis was carried out to estimate Odds Ratios (OR) and 95% Confidence Intervals (95% CI) for the association between participants’ sociodemographic, behavioral factors, and clinical factors with T. vaginalis infection. Results: Median age of study participants was 33 years (ranging from 18 to 50). The overall prevalence of T. vaginalis infection was 1.3% (n = 20). Several factors were independently associated with T. vaginalis infection, such as self-reporting as black or Pardo for ethnicity (OR = 2.70; 95% CI 1.03‒7.08), smoking (OR=3.18; 95% CI 1.23‒8.24) and having bacterial vaginosis (OR = 4.01; 95%CI = 1.55–10.38) upon enrollment. A protective effect of higher educational level (having high school degree) was observed (OR = 0.16; 95% CI 0.05‒0.53). Conclusions: Our data suggest that screening programs to correctly detect T. vaginalis infection can be helpful to guide prevention strategies to the community. Our study supports an association between abnormal vaginal microbiota and T. vaginalis infection.
Keywords: Bacterial vaginosis; Prevalence; Risk factors; Trichomonas vaginalis